2015
DOI: 10.1080/21528586.2014.989783
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sport participation on gender relations: Case studies of female footballers in Johannesburg and Cape Town, South Africa

Abstract: South Africa has progressive political policies concerning women with a high percentage of women in political positions, while simultaneously having some of the worst indicators of gender relations internationally, including high rates of rape and domestic violence. This article examines how participation in football can challenge hegemonic masculinity in South African society and sport through comprehensive case studies of women's football in the townships of Johannesburg and Cape Town. Internationally, sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…For young girls, it means access to play with boys and gain physical skills. For others, it means being elected into a leadership position within different spheres of influence, although such mainstreaming of gender, inevitably disadvantages females as it takes place in engendered spaces (Connell, 2009;Chawansky, 2011;Ogunniyi, 2013Ogunniyi, , 2015. The research findings reflect how females can mobilise support in the broader community by capitalising on her role as coach and "community builder" by teaching life lessons to children or providing emotional support.…”
Section: Barriers Limitations and Opportunities Barriers And Limitationsmentioning
confidence: 82%
See 3 more Smart Citations
“…For young girls, it means access to play with boys and gain physical skills. For others, it means being elected into a leadership position within different spheres of influence, although such mainstreaming of gender, inevitably disadvantages females as it takes place in engendered spaces (Connell, 2009;Chawansky, 2011;Ogunniyi, 2013Ogunniyi, , 2015. The research findings reflect how females can mobilise support in the broader community by capitalising on her role as coach and "community builder" by teaching life lessons to children or providing emotional support.…”
Section: Barriers Limitations and Opportunities Barriers And Limitationsmentioning
confidence: 82%
“…Socio-cultural barriers remain a pervasive theme in preventing equitable gender participation in structured physical activities for Xhosa-speaking women in the Eastern Cape Province (Walter and Du Randt, 2011). Ogunniyi (2013Ogunniyi ( , 2015 conducted critical feminist research in the soccer domain and identified intersectional ideologies that inform socio-cultural and political constraints for women and girls despite sporadic agency and resistance.…”
Section: Socialisationmentioning
confidence: 99%
See 2 more Smart Citations
“…Their participation in the study is in the context of their experiences during the COVID-19 pandemic as professional players of that particular code of sport. Like most codes of sport (with the exception of netball) in which females participate in South Africa, there is a wide inequality gap between males and females (Ogunniyi 2015). A good example are the respondents in this study who were professional female players at national level in both soccer and rugby but they were not in possession of contracts.…”
Section: Introductionmentioning
confidence: 94%